P112 Activation of PIK3CA in a model of endometriosis may shed light on the pathogenesis of ovarian clear cell adenocarcinoma. (1st November 2019) - Barbara, CF; King, C; Jimenez-Linan, M; Brenton, J; Charnock-Jones, DS
Abstract : Introduction/Background: Activating PIK3CA mutations are described in one third of ovarian clear cell adenocarcinomas (OCCA), an endometriosis-associated cancer, and are likely early events its development. To better characterise PIK3CA -mutated OCCA, we designed a xenograft model: we genetically modified human endometrium ex vivo, implanted it in an immunocompromised mouse, and studied the consequences of PIK3CA activation. Methodology: We co-transduced healthy human endometrium with luciferase ( in vivo reporter) lentivirus and either non-targeting control or PIK3CA activation lentivirus; this was implanted in Balb/c nu/nu mice. We monitored lesion size and luminescence and examined histology of 9 paired replicates. We performed RNA sequencing of 3 paired matched replicates and used DeSeq2 and PANTHER for differential expression and gene ontology (GO) analysis respectively. Results: Lesions survived up to 41 days. There was large variation in size and luminescence. Most lesions demonstrated endometrial-type glands in decidualised stroma. Three of 9 PIK3CA lesions, but no controls, showed well-defined hyalinsed stroma with inflammatory infiltration and no endometrial-type glands. Six of 9 PIK3CA lesions, but 1 control lesion, had inflammatory infiltration within the lesion (figure 1). P-value distribution histogram showed PIK3CA activation causes significant differential expression. 620 genes were differentially regulated (Padj ≤0.05, figure 2). The 2 most significantly enriched GO categories were metalloendopeptidase inhibitor activity (24.37-fold enrichment, Padj=7.06E-04) and metallopeptidase activity (5.15-fold enrichment, Padj=1.27E-04). GO analysis of the genes in the PI3K signalling pathway showed the 2 most significantly enriched transcripts encode the 5-Hydroxytryptamine 2A and 2B receptors (4.6-fold enrichment, Padj=4.95E-08 and 3.3-fold enrichment, Padj=0.00033 respectively). Conclusion: Constitutive PIK3CA activation caused significant differential expression and significant enrichment of metalloendopeptidase inhibitor activity and metallopeptidase activity. 5-hydroxytryptamine 2A and 2B receptor RNAs are also induced. Further research into the role of these molecules in OCCA and other cancers with activating PIK3CA mutations is warranted. Targeted inhibitors may have a role in management of these tumours. Disclosure: Nothing to disclose.